Penerapan Pembelajaran IPA Berbasis (PJBL) Pada Materi Sistem Pernafasan Manusia Menggunakan Media Torso Kreatif - Yulia Qur'aini; Fitrotun Amaniah; Khairun Nisak (Jurnal Pengabdian Pendidikan, 2025)
Absract: This study aims to describe the effectiveness of implementing the Project Based Learning (PJBL) model with creative torso media in science learning on the human respiratory system material in elementary schools. The research method used is descriptive qualitative. Data were collected through observation, concept understanding tests, interviews, and documentation. The results showed that PJBL with creative torso media effectively improved concept understanding, learning outcomes, and positive student responses. Students were actively involved, motivated, and enthusiastic during the learning process. The use of torso media helped students understand the structure and function of respiratory organs concretely. PJBL also encouraged the development of critical thinking skills, collaboration, responsibility, and student creativity. The implementation of PJBL with creative torso media is recommended as an alternative effective science learning model in elementary schools.